2020
DOI: 10.1111/age.12918
|View full text |Cite
|
Sign up to set email alerts
|

New genomic features of the polled intersex syndrome variant in goats unraveled by long‐read whole‐genome sequencing

Abstract: SummaryIn domestic goats, the polled intersex syndrome (PIS) refers to XX female‐to‐male sex reversal associated with the absence of horn growth (polled). The causal variant was previously reported as a 11.7 kb deletion at approximately 129 Mb on chromosome 1 that affects the transcription of both FOXL2 and several long non‐coding RNAs. In the meantime the presence of different versions of the PIS deletion was postulated and trials to establish genetic testing with the existing molecular genetic information fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
7
16
0
Order By: Relevance
“…Our GWAS and fine-mapping results were consistent with the two recent research results from Switzerland and China that used long-read whole-genome sequencing of two genetically female goats (a PIS-affected and a horned control) and whole-genome selective sweep of intersex goats from China, respectively [15,16] . Although the results of the three groups are consistent, our study is different from the other two studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our GWAS and fine-mapping results were consistent with the two recent research results from Switzerland and China that used long-read whole-genome sequencing of two genetically female goats (a PIS-affected and a horned control) and whole-genome selective sweep of intersex goats from China, respectively [15,16] . Although the results of the three groups are consistent, our study is different from the other two studies.…”
Section: Discussionsupporting
confidence: 89%
“…A 1.8 kb insertion in the 3' untranslated region (3' UTR) of RXFP2 has been identified to be associated with the horn/polledness of sheep [13] ; RXFP2 pseudogenization has been identified in Moschidae and Hydropotinae [12] , and a 212 bp insertion near gene OLIG1 (~65 kb away) was found to produce hornless cattle [14] . Recently, two groups reported that a novel intersexuality-associated variant consisting of ∼0.48 Mb duplicated fragment (including ERG and KCNJ15) downstream of the ∼20 Mb PIS region was reversely inserted into the PIS locus of goat [15,16] . However, the development of polledness trait in goats is very special because it is closely related to intersexuality, which increases the difficulties in the identification of hornless-related genes.…”
Section: / 22mentioning
confidence: 99%
“…This syndrome is a disorder of sexual development showing an association with the polled phenotype and intersexuality. PIS is caused by a 10-kb deletion and a 480-kb insertion containing the genes ERG and KCNJ15 leading to a complex rearrangement ( Simon et al, 2020 ). In cattle, polledness is caused by complex duplication variants on BTA1 that leads to differences in gene expression ( Wiedemar and Drögemüller, 2015 ).…”
Section: Common Trait Selection Affects Similar Genes Across Livestock Speciesmentioning
confidence: 99%
“…Although PIS has been localized by predecessors, in recent studies, different versions of PIS sites have been discovered (Kijas et al., 2013; Simon et al., 2020). Therefore, the complex mechanism of sex reversal caused by PIS is currently unclear, and there are few studies on the gene expression levels of intersex goats.…”
Section: Introductionmentioning
confidence: 99%